Wireless NoC for VFI-Enabled Multicore Chip Design: Performance Evaluation and Design Trade-Offs - Kim, Ryan Gary; Wonje Choi; Guangshuo Liu; Mohandesi, Ehsan; Pande, Partha Pratim; Marculescu, Diana; Marculescu, Radu (IEEE transactions on computers, 2016)
Multiple Voltage Frequency Island (VFI)-based designs can reduce the energy dissipation in multicore chips. Indeed, by tailoring the voltages and frequencies of each VFI domain, we can achieve significant energy savings subject to specific performance constraints. The achievable performance of VFI-based multicore platforms depends on the overall communication backbone, which relies predominantly on Networks-on-Chip (NoCs). Traditionally mesh-based NoCs have been used in VFI-based systems. However, the mesh-based NoCs have large latency and energy overheads due to their inherently long multihop paths. Emerging paradigms such as the millimeter (mm)-wave small-world wireless Networks-on-Chip (mSWNoCs) have lately been observed to help reduce the impact of the communication backbone on the performance of the multicore chips. In this work, we demonstrate that not only do mSWNoC-enabled VFI designs mitigate some of the full-system performance degradation inherent in VFI-partitioned multicore designs, but they also help in eliminating it entirely for certain applications. We also demonstrate that the VFI-partitioned designs used in conjunction with a novel NoC architecture like mSWNoC can achieve significant energy savings while minimizing the impact on the performance for each application under consideration.